Restitution of Jewish Property in Northern Transylvania During the Early Postwar Years - Ionescu Stefan Cristian (Eastern European Holocaust Studies)
The restitution of Jewish property in the multiethnic region of Northern Transylvania faced numerous challenges during the first post-Holocaust years as a result of the complicated wartime history, postwar demographics, legal status, interethnic dynamics, and occasional violence. Having the lowest rate of survival among all Jewish communities in Romania, most of the region’s Jews died during the deportation and did not return to their native places to claim their properties. This impacted the extent of restitution of individual private property. Some of the Aryanized property was restituted to the Jewish survivors or their heirs because the wartime beneficiaries fled the country or renounced posession since they were afraid of potential negative consequences. Part of the restitution took place through court litigation and this gives researchers a chance to assess the extent of Jewish success in obtaining restitution. The Supreme Court decisions in restitution cases show that the Jewish plaintiffs were completely successful in their litigation based on law 645/1945 that cancelled the transactions with property Aryanized during the Hungarian rule of Northern Transylvania. This was a much higher success rate, compared to the general share of success for Jewish litigation at the entire country level – around 66 %.